The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1093/icvts/ivv162
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac surgery-associated acute kidney injury: risk factors analysis and comparison of prediction models

Abstract: The performance of known prediction models for AKI-D was found reasonably well in the prediction of KDIGO-AKI, with the model by Thakar having the highest predictive value in the discrimination of patients with risk for all KDIGO-AKI stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 24 publications
4
56
1
Order By: Relevance
“…The incidence of RRT was 10%, which is within the range reported by Kiers et al (9.3%) [11]. Kristovic noted an incidence of 3.5% in a retrospective study, which is much lower than the values assessed in the present study [12]. Finally, from 31,677 patients who underwent open-heart surgery, 555 (1.7%) patients developed severe AKI requiring dialysis [13].…”
Section: Discussionsupporting
confidence: 76%
“…The incidence of RRT was 10%, which is within the range reported by Kiers et al (9.3%) [11]. Kristovic noted an incidence of 3.5% in a retrospective study, which is much lower than the values assessed in the present study [12]. Finally, from 31,677 patients who underwent open-heart surgery, 555 (1.7%) patients developed severe AKI requiring dialysis [13].…”
Section: Discussionsupporting
confidence: 76%
“…6 This imposes a considerable economic burden on the health care system. Prior studies have demonstrated prolonged duration of CPB as a risk factor for ARF 3,7,8,[10][11][12] ; however, CPB time is frequently dichotomized at heterogeneous time points.…”
Section: Discussionmentioning
confidence: 99%
“…Higher preoperative sCr was considered as an independent risk factor for postoperative AKI. [36] The studies of Christenson, [33] Prowle et al [18] and Billings et al [21] did not exclude patients with preoperative renal dysfunction which was diagnosed by elevated sCr and these 3 studies showed no protective effect of PST on renal outcome. Billings et al [21] even found that PST was associated with increased sCr on postoperative day 2 and AKI occurred in more patients with preoperative chronic kidney disease(CKD) randomized to atorvastatin than placebo.…”
Section: Discussionmentioning
confidence: 99%